2015
DOI: 10.1016/j.jtcvs.2014.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of paravalvular leak: Long-term results in a single-center experience (up to 14 years)

Abstract: The operative mortality of surgical treatment of paravalvular leak is still high. Long-term outcomes remain suboptimal in these challenging patients, especially in the presence of multiple previous cardiac operations and associated co-pathologies. These results support the importance of alternative therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 16 publications
5
89
1
2
Order By: Relevance
“…Operative mortality ranges from 6% to 13 % (1-4). The median EuroSCORE II of our cohort (9.5%) falls within the range (7.5% to 9.6%) described by other contemporary series (3,4). Residual mitral PVL has been reported in 2% to 22% of patients following surgical correction (1,3,4).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Operative mortality ranges from 6% to 13 % (1-4). The median EuroSCORE II of our cohort (9.5%) falls within the range (7.5% to 9.6%) described by other contemporary series (3,4). Residual mitral PVL has been reported in 2% to 22% of patients following surgical correction (1,3,4).…”
Section: Discussionsupporting
confidence: 78%
“…The median EuroSCORE II of our cohort (9.5%) falls within the range (7.5% to 9.6%) described by other contemporary series (3,4). Residual mitral PVL has been reported in 2% to 22% of patients following surgical correction (1,3,4). Recurrence of PVL has been cited to occur at a rate of 4% per patient-year (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent TAVR and surgical PVR studies report that mild PVR after surgical AVR is not uncommon, with reported PVR rates between 1% and 47%. 9,[18][19][20] In the most frequently cited studies, conventional surgical AVR has a reported PVR incidence between 2% and 17%. 6,7,12,21 In comparison, the overall incidence of PVR 1þ or greater after AVR in the current study was 2.2%.…”
Section: Previous Studies Of Surgical Paravalvular Regurgitationmentioning
confidence: 99%
“…Advances in surgical valve technology, refinement of surgical technique, and experience have most likely contributed to contemporary PVR rates at or below the lower end of the historical reported incidence, even with ever-improving echocardiographic technology. In a recent study, Taramasso and colleagues 19 reported that the surgical treatment of PVR is still high and that long-term outcomes remain suboptimal. Future comparisons with TAVR data and emerging technologies such as sutureless AVR and percutaneous MVR should consider the significantly lower contemporary rate of PVR after surgical AVR and MVR.…”
Section: Previous Studies Of Surgical Paravalvular Regurgitationmentioning
confidence: 99%